CONTENT AND LANGUAGE ORIENTED ASPECTS OF TEACHING ENGLISH - Ravshanqulov, Otabek (Журнал иностранных языков и лингвистики, 2021)
ABSTRACT This article studies teaching methods and the teacher`s role in traditional methods of teaching through lectures where we find one-sided discourse from the teacher and passive response or blind acceptance by the students. Much is left to the imagination of the teacher and the students and, if possible, to the interpretative ability of the students. In new methods, the teacher`s skill in maki ng the learner feel the exprience of the writer contributes to effective learning. The teacher has to have the ability to apply new techniques suitable to the learning of English literature in content-oriented and language-oriented aspects. The teacher has to train the minds of the learners to grasp the writer`s vision, approaches and the beauty of language as well as the use of new words; he requires such new skills. The teacher must have an ability to connect the non -native aspect in the content and language with the real-life situation. Keywords: English teacher, learners, structures, languages.